Parents' and children's power effectiveness during polyadic family conflict: Process and outcome. Issue 1 (25th September 2018) - Della Porta, Sandra; Howe, Nina; Persram, Ryan J.
Abstract: Parent–child power effectiveness was investigated during naturally occurring polyadic family conflict with young children involving three or more family members. In 35/39 families, 210 conflict sequences were identified and coded for type of power, power effectiveness, and conflict outcome. Effective use of power overall and by each partner was assessed using two methods: microscopic (target's response to an actor's power move during the process of conflict) and macroscopic (power moves related to conflict outcome). Actor findings revealed that parents were more effective using certain types of power microscopically (i.e., simple, legitimate, reward) and macroscopically (i.e., simple, legitimate, questioning), whereas children were more effective using reward power macroscopically. Our findings support the unique qualities of the parent–child relationship and the complex context of polyadic family conflict. The study contributes to the literature on the socialization of young children in the family context.